2008
DOI: 10.1007/s00420-008-0371-8
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic action on steroid hormone synthesis and sulfonation the example of lead and polychlorinated biphenyls

Abstract: Our results suggest that PCBs and Pb act on steroid hormone metabolism with different effects and only partially using the same hormone pathways; they may cause changes in endogenous hormone homeostasis and interfere with the xenobiotic phase II of detoxification. PCBs interfere on a larger number of steroids and cause more significant effects than Pb. It is likely that different mechanisms are involved in steroid hormone metabolism interference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The reduced urinary excretion of total 17-KS observed in our study is in agreement with the report by Romeo et al [ 6 ] in subjects of the general population resident in urban areas near an industrial plant producing PCBs. These subjects had a mean serum concentration of total PCBs of 61.9 ng/mL calculated on 24 congeners, higher than the 10.04 ng/mL, calculated on 33 congeners, observed in our workers exposed to PCBs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reduced urinary excretion of total 17-KS observed in our study is in agreement with the report by Romeo et al [ 6 ] in subjects of the general population resident in urban areas near an industrial plant producing PCBs. These subjects had a mean serum concentration of total PCBs of 61.9 ng/mL calculated on 24 congeners, higher than the 10.04 ng/mL, calculated on 33 congeners, observed in our workers exposed to PCBs.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, in some studies on experimental animals administered mixtures of PCBs by different routes, an increase in serum levels of corticosterone was reported, in others a reduction in the serum levels of corticosterone, dehydroepiandrosterone (DHEA) and DHEA sulfate (DHEA-S), while in yet other studies no effect was observed [ 4 ]. In humans, too, environmental exposure to PCBs has revealed different effects, ranging from a positive association with serum DHEA-S in children, to a reduction of the urinary metabolites of 17-ketosteroids (KS) and 17-hydroxycorticosteroids (17-OHCS), of sulfonated compounds for 17-OHCS and of the sulfonation percentage of 17-KS and 17-OHCS [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the findings in this study are not conclusive of cause and effect, they contribute to the significant body of evidence that organohalogen pollutants cause endocrine disruption in seals, from the subcellular level (hormone receptor interactions and altered hormone biosynthesis and metabolism (Troisi and Mason 2000;Troisi et al 2001;Li et al 2003;Routti et al 2010), tissue-organ level (uterine deformities; Olsson et al 1974;Helle 1980;Baker 1989), individual level (reproductive failure; Reijnders 1986), and ultimately at the population level (localised extinction of Baltic Sea ringed and Grey seals; Helle 1980;Helle et al 1990;Harding and Härkönen 1999). Although the modeof-action whereby PCBs disturb hormone homeostasis is unclear, it is likely that disruption of steroid biosynthetic pathways, and the interference with hormone binding to plasma transport proteins and hormone receptor proteins are involved (Sanderson 2006;Romeo et al 2009;Hampl et al 2014). Despite international bans of POPs, PCBs continue to contaminate apex predators, and their levels in Baltic and Svalbard seals remain in the same range as those reported in this study (Bjurlid et al 2018).…”
Section: Discussionmentioning
confidence: 49%
“…In mammals, PCBs interfere with the biosynthesis, transport, and metabolism of steroids by altering the activity of cytochrome P450 isozymes, such as 5α-reductase, 3α-, 11β-, and 17β-hydroxy steroid dehydrogenases (Sanderson 2006;Romeo et al 2009;Hampl et al 2014). In vitro studies of hepatic microsomal hormone metabolism in harbour and grey seals have shown these species have the capacity for 6βand 2β-hydroxylation of T4 and 6β-and 16α-hydroxylation of P4 indicative of CYP1A, CYP3A, and CYP2B isozyme activity, as occurs in most mammals in biosynthesis (Troisi and Mason 2000;Li et al 2003).…”
Section: Grey Seal Malesmentioning
confidence: 99%
“…The factory was in operation from 1930s to the 1980s. Totally 24 PCBs were determined in blood and the mean blood level in the exposed group was 61.9 µg/l (range 17.5-138) as compared to 3.2 µg/l (range 0.8-10.4) in the control group (318).…”
Section: Some Other Endocrine/metabolic Effectsmentioning
confidence: 89%